Os referenciais de construção identitária dos alunos do 6º ano do colégio São Luís e a Pedagogia Inaciana como fundamento influenciador - Oliveira, Rosilene Aparecida de (Universidade do Vale do Rio dos Sinos, 2023)
Considering contemporaneity and the way of being of teenagers at this time, the objective of this article was to understand and categorize references that influence the identity construction of this public, specifically of students in the 6th year of Elementary School II, at Colégio São Luís, belonging to the Jesuit Education Network (RJE), located in the city of São Paulo. The study was developed using a qualitative descriptive methodology in which, from the authors studied, a categorization of influencing references and their impact on the adolescent's education was obtained. Finally, using documents related to Ignatian Pedagogy, which guide the education of RJE schools, fundamental points were raised capable of reinforcing the application of an integral education, which develops and improves the cognitive, socio-emotional and spiritual- religious dimensions of these teenagers.
Keywords: Adolescência; Identidade; Influenciadores; Pedagogia Inaciana; Adolescence; Identity; Influencers; Ignatian Pedagogy